Olivier de Clisson and political society in France under Charles V and Charles VI - Henneman, John Bell, 1935- (University of Pennsylvania Press, 1996)
Selected by Choice magazine as an Outstanding Academic Title.
Keywords: Clisson, Olivier de, -- 1336-1407.; Clisson, Olivier de, -- 1336-1407; Clisson, Olivier de, -- (1336-1407); Clisson, Oliver de.; France -- Politics and government -- 1328-1589.; Nobility -- France -- Brittany -- Biography.; Soldiers -- France -- Biography.; Hundred Years' War, 1339-1453 -- Biography.; France -- Relations -- England.; England -- Relations -- France.; Social history -- Medieval, 500-1500.; Military biography -- France.; Noblesse -- France -- Bretagne -- Biographies.; Militaires -- France -- Biographies.; Guerre de Cent Ans, 1339-1453 -- Biographies.; Histoire sociale -- 500-1500 (Moyen Âge); France -- Politique et gouvernement -- 1328-1589.; France -- Relations -- Angleterre.; Angleterre -- Relations -- France.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Europe -- France.; HISTORY -- Medieval.; International relations; Nobility; Politics and government; Soldiers; England; France; France -- Brittany; Politik; Militär; Marmousets; Adel; Frankreich; Honderdjarige oorlog.; Hofcultuur.; Noblesse -- France.; Guerre de Cent ans (1337-1453); Armagnacs et Bourguignons.; Grande-Bretagne -- 1066-1485.; France -- 1364-1380 (Charles V); Bretagne (France) -- 1341-1532.; 1328-1589; Electronic books.; Biography; Biographies; Biographies.